Experimental Trawling In Hirakud Reservoir - GEORGE, V C; DAWSON, PERCY; KHAN, A A; VARGHESE, M D (Fishery Technology, 2017)
Results of trawl fishing experiments conducted in Hirakud reservoir are discussed. Trawling has been found to be efficient than conventional gear in removing predators and trash fishes especially of the bottom. This method can be of much help in controlling the proliferation of such fishes in many Indian reservoirs.